A Sociolinguistic Analysis of Power Relations and Politeness Strategies Used by the Main Character in Legally Blonde (2001) - Aulia Monica Tambunan; Partohap Saut Raja Sihombing; David Togi Hutahaean (International Journal of Technology and Education Research, 2026)
This research analyzes the power relations and politeness strategies used by the main character, Elle Woods, in Legally Blonde (2001) from a sociolinguistic perspective. The objectives of this study are to identify the types of politeness strategies used by Elle Woods and to examine how power relations influence her language choices in interaction. This research employed a descriptive qualitative method. The data were taken from the dialogues spoken by Elle Woods in the movie Legally Blonde (2001) and its script. The data were collected through observation and note-taking techniques, then analyzed using the politeness theory proposed by Brown and Levinson (1987). The findings show that all four politeness strategies were used by the main character, namely bald on record, positive politeness, negative politeness, and off-record strategy. Among them, positive politeness appeared most frequently because Elle often used friendly, supportive, and cooperative expressions in her interactions. The findings also reveal that power relations significantly influenced the choice of politeness strategies. Positive politeness was mostly used in equal power relations, while negative politeness appeared more frequently in interactions involving higher authority figures. Bald on record strategy was commonly used in situations requiring directness and confidence. The study concludes that politeness strategies reflect social relationships, power dynamics, and communicative goals within interaction. Therefore, the movie provides valuable insight into the relationship between language, politeness, and power in sociolinguistic studies.